Jewish Cultural Traditions within a Modernising Early Soviet Framework: Y. Goldberg's 1935 Yiddish Othello. (2nd January 2022) - Kahn, Lily
ABSTRACT: This article explores the Yiddish Othello translation produced under Soviet state auspices by the Russian Jewish folklorist Y. Goldberg and published in 1935 by the State Press of Belorussia. It is the first study devoted to Goldberg's Yiddish Shakespeare translations. The article will consider the ways in which Goldberg's translation reflects a tension between a modernising Soviet ideology on the one hand, and traditional Eastern European Jewish culture on the other. The former is manifested in the translation through its use of an accessible Soviet Yiddish style; through Goldberg's avoidance of citations from classical Jewish sources; and through his characterisation of Desdemona as an admirably modern and progressive woman. The latter is manifested through domesticating elements, specifically allusions to Jewish traditions such as oylemhaze 'the Present World', taneysim 'fast days', and yichus (Jewish ancestral pedigree); and references to Eastern European Jewish realia (e.g. herring and turnips). Examination of Goldberg's work provides a fascinating perspective on an understudied aspect of the Jewish relationship with Shakespeare. The article fits into the wider context of Jewish language, literature, and culture in the early Soviet period, and of multicultural and minority-language Shakespeare more broadly.